Implementation of Educational Technology as a Media Teaching Material to Improve Student Learning Outcomes - Muhammad Nuzli; Ima Trisna Dewi Ramadani; Marwiyah; Ariyanto; Hamisah (Indonesian Journal of Educational Science and Technology, 2023)
This study aims to determine the function and role as well as the implementation of educational technology through teaching materials in improving student learning outcomes at 28 Merangin State Junior High School. The research was carried out using a qualitative type with the results of research that technology acts as a medium for teaching materials in the learning process as a basis for learning, by writing an outline of learning material on the available blackboard. The implementation of the inhibiting factor in improving the learning outcomes of Class VIII students of Merangin 28 Public Junior High School in the subject of Islamic Religious Education and ethics is the lack of the number of technological facilities available at Merangin 28 State Junior High School, for this reason the teacher must be able to use the available technology as a interesting teaching material media by combining it using learning methods.